O Logos se fez dia-logos :economia do Logos encarnado e diálogo inter-religioso em busca da paz em Claude Geffré - Gomes, Tiago de Fraga (2020)
The present doctoral research, following the intellectual itinerary of Claude Geffré, aims to address the theme of the Logos that was become dia-logos – ο Λόγος έγινε διάλογος – in order to work on the economy of the incarnate Logos as the Christological foundation for a collaborative dialogue between religions in search of peace. The play on words Λόγος and διάλογος intends to underline the dialogical perspective prompted by the eternal Logos of God who was become flesh and revealed the profound nature of the divine mystery through a fraternal dialogue. It is based on the premise that in the face of today’s religious pluralism, a pluralistic hermeneutics of the economy of revelation, starting from the Logos incarnate, fosters a sense of otherness and of mutual collaboration between religions and underpins the building of a culture of peace and non-violence. It is also proposed that the use of the figure of Jesus of Nazareth, as a paradigm of pacification, is a pertinent alternative to inspire the creative and non-violent resolution of conflicts in today’s society. The argument is based on the hermeneutic Logos, the methodological foundation of a hermeneutical rationality in theology and of a plural reading of the economy of Christian revelation. It follows with the dialogical Logos, a condition for a dialogical opening between religions, and concludes with the collaborative Logos, a fundamental disposition for a collaborative dialogue between religions in favor of building a culture of peace and non-violence.